Leveraging Artificial Intelligence as a Strategic Enabler in Industrial Multinational Corporations : Action Research in MNC X - Roiha, Sonja (My University, 2026)
In this thesis, the strategic implications of artificial intelligence (AI) adoption in organizations are examined, with particular focus on long-term competitiveness, organizational capabilities, and change management. As investments in AI continue to increase, organizations face growing pressure to adopt AI-driven solutions not only to enhance operational efficiency, but also to remain competitive and attractive as employers and business partners. Despite this development, existing research on AI strategy remains relatively fragmented and often emphasizes short-term benefits rather than long-term organizational transformation. This study addresses that gap by conceptualizing AI as a comprehensive organizational change process rather than a purely technological or IT-driven initiative. The main research question explores how artificial intelligence can be strategically integrated into an industrial multinational corporation (MNC) to sustain long-term competitive advantage. More specifically, the study examines which strategic risks and implementation challenges influence the realization of value from AI, what forms of competitive advantage AI can enable in the industrial context, and which organizational capabilities are required to operationalize an AI strategy. In addition, this thesis analyses how AI can be embedded into the business strategy of the case company, MNC X, to achieve sustainable competitive advantage. This study adopts a qualitative action research approach, drawing both on academic literature and empirical data to analyse AI adoption from strategic and organizational perspective. The theoretical framework builds on research related to strategic change, dynamic capabilities, competitive advantage, and risk management. By combining theoretical insights with empirical observations, the study enables a critical examination of both conceptual foundations and practical implementation challenges. This approach facilitates the development of practically applicable knowledge while remaining grounded in existing academic discourse. The findings indicate that AI adoption can significantly influence long-term competitiveness and should be treated as a strategic, organization-wide transformation rather than a separate efficiency initiative. Clear governance structures, strong top management commitment, cross-functional coordination, and continuous capability development emerge as central enablers of successful AI integration. The results further suggest that organizations failing to engage proactively with AI risk developing an outdated organizational image, potentially weakening brand perception, employer attractiveness, and strategic agility. In response to these findings, the study develops structured managerial tools to support strategic AI integration, including an AI strategy framework, an AI operating model, and a phased implementation roadmap. These tools translate strategic objectives into concrete actions, clarify ownership and governance structures, and support capability development at strategic, structural, and individual levels. By operationalizing AI strategy through systematic frameworks and emphasizing human-machine complementarity aligned with Industry 5.0 principles, the study extends existing research from conceptual discussion toward practical execution. Overall, this thesis contributes to the emerging field of long-term AI strategy by bridging strategic management theory and organizational practise. By developing structured frameworks and governance mechanisms, the study translates abstract strategic principles into actionable implementation tools. It thereby offers an organization-wide perspective on AI adoption and provides practical guidance for transforming AI from isolated experimentation into a source of sustained competitive advantage.

Tässä tutkielmassa tarkastellaan tekoälyn (AI) käyttöönoton strategisia vaikutuksia organisaatioissa keskittyen erityisesti pitkän aikavälin kilpailukykyyn, organisaation kyvykkyyksiin ja muutosjohtamiseen. Tekoälyinvestointien kasvaessa organisaatioihin kohdistuu yhä suurempi paine hyödyntää tekoälyratkaisuja sekä prosessin tehokkuuden parantamiseksi että säilyttääkseen kilpailukykynsä ja houkuttelevuutensa työnantajana ja liikekumppanina. Nykyinen tekoälystrategiaa koskeva tutkimus on kuitenkin hajanaista ja painottuu usein lyhyen aikavälin suorituskykyhyötyihin kestävän organisaatiomuutoksen sijaan. Tämä tutkimus vastaa tähän tutkimusaukkoon tarkastelemalla tekoälyä kokonaisvaltaisena, organisaation laajuisena strategisena kyvykkyytenä pelkän teknologisen tai IT-lähtöisen aloitteen sijaan. Tutkielman päätutkimuskysymys keskittyy siihen, miten tekoäly voidaan integroida strategisesti teolliseen monikansalliseen yritykseen (MNC) pitkän aikavälin kilpailuedun turvaamiseksi. Erityisesti tutkimuksessa keskitytään siihen, millaiset strategiset riskit ja toteutushaasteet vaikuttavat tekoälyn tuottaman arvon realisoitumiseen, millaisia kilpailuetuja tekoäly voi mahdollistaa teollisella sektorilla sekä millaisia organisatorisia kyvykkyyksiä tekoälystrategian operatiivinen toimeenpano edellyttää. Lisäksi tarkastellaan, miten tekoäly voidaan liittää osaksi tapausyrityksen, MNC X:n, liiketoimintastrategiaa kestävän kilpailuedun saavuttamiseksi. Tutkimus toteutetaan laadullisena toimintatutkimuksena, joka yhdistää akateemista kirjallisuutta sekä empiiristä aineistoa analysoidakseen MNC X:n tekoälyn käyttöönottoa strategisesta ja organisatorisesta näkökulmasta. Analyysi perustuu keskeisiin teorioihin sekä tutkimuslöydöksiin, jotka koskevat strategista muutosta, kyvykkyyksien kehittämistä ja riskejä. Lähestymistapa mahdollistaa sekä teoreettisten näkökulmien että käytännön haasteiden kriittisen tarkastelun, ja sen myötä uuden käytännöllisesti sovellettavissa olevien ehdotusten kehittämisen yhdessä olemassa olevan tutkimuksen kanssa. Tutkimuksen keskeiset tulokset osoittavat, että tekoälyn käyttöönotto vaikuttaa organisaation pitkän aikavälin kilpailukykyyn ja siihen tulee suhtautua strategisena, koko organisaation kattavana muutosprosessina, ei erillisenä tehokkuushankkeena. Tulokset korostavat selkeiden hallintorakenteiden, johdon vahvan sitoutumisen ja jatkuvan kyvykkyyksien kehittämisen merkitystä strategiaa kehittäessä ja riskejä hallittaessa. Lisäksi löydökset viittaavat siihen, että organisaatiot, jotka eivät aktiivisesti sitoudu tai hyödynnä tekoälyä, saattavat vaarantaa maineensa vanhentuneina toimijoina, mikä voi heikentää brändiä sekä vetovoimaa sidosryhmien näkökulmasta. Kaiken kaikkiaan tämä tutkimus laajentaa rajoittunutta pitkän aikavälin tekoälystrategiaa käsittelevää tutkimusta tarjoamalla kokonaisvaltaisen organisaatiotason näkökulman tekoälyn käyttöönoton strategisiin vaikutuksiin. Näiden havaintojen pohjalta tutkimuksessa kehitetään jäsenneltyjä johtamisen työkaluja strategisen tekoälyintegraation tueksi, mukaan lukien tekoälystrategiakehys, tekoälyn toimintamalli sekä vaiheittainen käyttöönoton tiekartta. Nämä työkalut muuntavat strategiset tavoitteet konkreettisiksi toimenpiteiksi, selkeyttävät omistajuutta ja hallintorakenteita sekä tukevat kyvykkyyksien kehittämistä strategisella, rakenteellisella ja yksilötasolla. Operationalisoimalla tekoälystrategian systemaattisten viitekehysten avulla ja korostamalla Industry 5.0 periaatteiden mukaista ihmisten ja koneen välistä täydentävyyttä tutkimus vie keskustelua käsitteelliseltä tasolta kohti käytännön toteutusta. Kaiken kaikkiaan tämä tutkimus edistää pitkän aikavälin tekoälystrategiaa koskevaa tutkimuskeskustelua yhdistämällä strategisen johtamisen ja organisaatiokäytännöt.
Keywords: Artificial intelligence (AI); AI Strategy; Organizational Change; Long-Term Competitiveness; AI Implementation